Acondicionamiento del tren inferior y su incidencia en el salto vertical en jóvenes - Raigoza Montenegro, Elian Santiago (2025)
This research evaluated the effect of a physical conditioning program aimed at developing lowerbody explosive power in a young adult population, with an emphasis on improving vertical jump. The study, conducted within the academic context of sports science training, aimed to determine the effectiveness of a structured training protocol incorporating strength and plyometric components to enhance performance in this fundamental motor skill across various sports disciplines. The methodological design employed an experimental approach with control groups, analyzing 32 participants equally divided between an intervention group and a control group that maintained their usual routine. Performance was assessed using standardized jump capacity tests, employing specialized technology for the objective measurement of biomechanical parameters. The findings demonstrated significant increases in test scores following the implementation of the training program, with an average improvement of 6.77 cm in vertical jump height. These results are supported by statistical analysis that showed significant differences between initial and final measurements in the explosive strength indicators evaluated. The evidence obtained supports the need to implement specialized physical conditioning programs for young athletes, highlighting the importance of a methodological approach that integrates the development of conditioning abilities and specific technical aspects. The findings have significant implications for the field of sports training, suggesting the advisability of incorporating these principles into athletes' training and physical preparation during their developmental years. This work contributes to the field of sports pedagogy by providing empirical evidence on effective strategies to improve physical performance in young people and by scientifically validating the application of specific neuromuscular conditioning protocols.